Factors Influencing Compliance Among Indonesian Construction Service Business Entities: A Systematic Literature Review - Agus Gendroyono; Agus Taufik Mulyono; Oei Fuk Jin; Endah Murtiana Sari (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
Compliance among Construction Service Business Entities (CSBEs) is essential for ensuring the delivery of safe, high-quality, and legally compliant construction projects while strengthening governance within the construction industry. Despite continuous regulatory reforms in Indonesia, maintaining consistent compliance among CSBEs remains a significant challenge due to the interaction of regulatory, organizational, and external factors. This study aims to identify and synthesize the factors influencing the compliance level of Indonesian Construction Service Business Entities through a Systematic Literature Review (SLR). The review followed the PRISMA 2020 guidelines and systematically searched publications indexed in Scopus, Web of Science, ScienceDirect, SpringerLink, Taylor & Francis Online, Emerald Insight, Google Scholar, Garuda, and SINTA published between 2015 and 2025. A total of 486 records were initially identified. After duplicate removal and eligibility screening, 52 studies met the inclusion criteria and were included in the qualitative synthesis. The selected studies were analyzed using content analysis and thematic synthesis to identify the dominant determinants of organizational compliance. The findings reveal nine principal factors influencing compliance, namely regulatory framework, government supervision and enforcement, human resource competency, organizational capacity, financial capability, information technology adoption, organizational culture, management commitment, and safety and environmental factors. Among these, regulatory quality, government supervision, human resource competency, and management commitment consistently emerged as the most influential determinants reported across the reviewed studies. This review provides a comprehensive conceptual framework that supports policymakers, researchers, and construction industry stakeholders in strengthening compliance strategies, improving governance systems, and enhancing the sustainability and competitiveness of Indonesia's construction sector.